Asuhan Keperawatan Pada Ibu Dengan Abortus Imminens - Nur Soliha; Ira Sukyati (AKPER Pasar Rebo, 2019)
Imminent abortion is spotting bleeding that shows a threat to the survival of a pregnancy (Yeyeh, 2010). The purpose of writing this journal is to get real experience in providing nursing care to mothers with imminent abortion. The method of this journal is descriptive narrative with data collection techniques through case studies by providing nursing care. The rate of spontaneous abortion is around 11 million out of 208 million pregnancies in the world, that is almost 90% occur unsafem thus contributing 11%-13% of maternal deaths (Ministry of Health, 2015). The results of this research is : patient who have imminent abortion get a weakness, patient complained have a bleeding such as menstruation, patients said dizzy, patient complained of pain in the lower abdomen, patients said pain like being stabbed, the patient said the scale of pain 6, pain felt settled and lost.